PCR with Paracoccidioides brasiliensis Specific Primers : Potential Use in Ecological Studies (1999)
ABSTRACT: The precise microenvironment of Paracoccidioides brasiliensis has not yet been discovered perhaps because the methods used are not sensitive enough. We applied to this purpose the polymerase chain reaction (PCR) using three sets of specific primers corresponding to two P. brasiliensis genes. This fungus as well as several other fungi, were grown and their DNA obtained by mechanical disruption and a phenol chloroform isoamylalcohol-based purification method. The DNA served for a PCR reaction that employed specific primers from two P. brasiliensis genes that codify for antigenic proteins, namely, the 27 kDa and the 43 kDa. The lowest detection range for the 27 kDa gene was 3 pg. The amplification for both genes was positive only with DNA from P. brasiliensis; additionally, the mRNA for the 27 kDa gene was present only in P. brasiliensis, as indicated by the Northern analysis. The standardization of PCR technology permitted the amplification of P. brasiliensis DNA in artificially contaminated soils and in tissues of armadillos naturally infected with the fungus. These results indicate that PCR technology could play an important role in the search for P. brasiliensis’ habitat and could also be used in other ecological studies.